2023
DOI: 10.3389/fpsyg.2023.1160591
|View full text |Cite
|
Sign up to set email alerts
|

Playing at the school table: Systematic literature review of board, tabletop, and other analog game-based learning approaches

Carla Sousa,
Sara Rye,
Micael Sousa
et al.

Abstract: The unique characteristics of games have led scientific research to increasingly focus on their potential role in learning processes. Currently, their effectiveness in fostering experiential learning and skill acquisition in several areas is already supported by the existing evidence, mainly about the potential of digital games. Paradoxically, the current post-digital era seems to have led to a growing popularity of analog games. The present Systematic Literature Review aimed to map the existing literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…This aligns with the research conducted by Pham Tien Thanh and Pham Thi Tham, underscoring the value of games in addressing students' psychological characteristics (Pham, 2018;Pham, 2017). Furthermore, Sousa et al (2023) agree with these findings, highlighting motivation and confidence as positive outcomes of games.…”
Section: Discussionsupporting
confidence: 82%
“…This aligns with the research conducted by Pham Tien Thanh and Pham Thi Tham, underscoring the value of games in addressing students' psychological characteristics (Pham, 2018;Pham, 2017). Furthermore, Sousa et al (2023) agree with these findings, highlighting motivation and confidence as positive outcomes of games.…”
Section: Discussionsupporting
confidence: 82%
“…Later, Sousa et al (2023) found that accessibility and inclusion were not frequently approached in a systematic literature review on analogue GBL. Despite the perception that the board game community is particularly welcoming and inclusive, it seems that these aspects are not a major focus in research.…”
Section: State Of the Art In Analogue Gaming Accessibilitymentioning
confidence: 99%
“…There has been an increasing interest in using analogue GBL to tackle different educational and developmental challenges in recent years (Maratou et al, 2023;Sousa et al, 2023a). This emergence of the analogue may be a natural response to over-digitization, digital fatigue and, at the same time, the technological barriers that exist in some educational contexts (Marenco, & Seidl, 2021;Sousa et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%